Contribution to Sustainable Development from the Indigenous Perspective: Existence through an Ethno-Educational Vision - Marín, Luisa Fernanda Zuluaga; Cuervo, Jimena Cardona (Journal of Ecohumanism, 2024)
Fifty-two years have passed since the first conference on "the Human Environment," convened by the United Nations, which referred to the human focus because anthropocentrism was still prevalent on the planet; such an observation is necessary in light of what the species' media intervention implies for the environment in the deterioration of environmental conditions, to the detriment of everyone's well-being, including, of course, other species and the mechanisms through which their life flows—this being a superior prerogative, at least from the perspective of legal rights, but ultimately also natural. In summary, this paper addresses the essential role of ethnoeducation in sustainable development, when it is feasible to achieve a consensus in the restoration from a broad dimension, also acknowledging that their ancestral constructs have much to contribute to a transitional social model that is conscious of the changes that must prevail in order to mitigate an environmental crisis in which human beings are deeply involved—as instigators but also as victims; the same crisis that has been analyzed since 1972, but with approaches in which the discourse has been restructured regarding the causes and the responsible actors, even acknowledging a perception of population sectors whose historical condition of marginalization has relegated them from an essential role in this process.